Recurrent periodontal abscess associated with "teeth as a tool" - G Subraya Bhat; Vishal Singh; K Mahalinga Bhat (Wolters Kluwer Medknow Publications, 2012)
We report an unusual case of recurrent periodontal abscess in a 31-year-old male electrician due to his habit of using his teeth as a tool for stripping electrical wires. The patient was not aware of the consequences of this habit. Clinically, there was presence of moderate depth of periodontal pocket around the tooth and, radiographically, there was a vertical defect mesial to the involved teeth. The patient was educated about the consequences of his habit and surgical treatment was undertaken. A papilla preservation flap with regenerative periodontal surgical procedure was done, orthodontic and restorative treatment was planned at the follow-up. This case highlights the importance of eliciting a proper and complete personal history, including occupational details. In our patient these details helped us correlate the destruction of the periodontium to the unusual etiology.